BTB Protein KLHL12 Targets the Dopamine D4 Receptor for Ubiquitination by a Cul3-based E3 Ligase - Rondou, Pieter (American Society for Biochemistry and Molecular Biology, 2008)
Dopamine receptors belong to the superfamily of G-protein-coupled receptors and are subdivided into D1-type (D1 and D5) and D2-type (D2, D3, and D4) receptors. The D4 receptor has a remarkable polymorphism in its third intracellular loop, which is under intensive investigation and which has been associated with, among other conditions, attention deficit hyperactivity disorder. Here, we demonstrate that KLHL12, a BTB-Kelch protein, specifically binds to this polymorphic region of the D4 receptor through its Kelch domain. Moreover, we show that KLHL12 also interacts with Cullin3 and thereby functions as an adaptor to target the D4 receptor to an E3 ubiquitin ligase complex. By ubiquitination assays in eukaryotic cells, we further demonstrate that overexpression of KLHL12 strongly promotes ubiquitination of the D4 receptor. In addition, we show that also other dopamine receptor subtypes undergo basal ubiquitination, but this is not affected by KLHL12. These data are the first to show ubiquitination of dopamine receptors and the first to identify a protein specifically interacting with the D4 polymorphism, thereby building up an E3 ligase complex with substrate specificity toward the D4 receptor.